Modeling the shrimp aquaculture wastewater pollutant removals by clam shell using structural equation model - N.D. Takarina; O.M. Chuan; A. Adiwibowo; M.A. Adidharma (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Aquaculture practices were emitting wastewater containing pollutants. The pollutants include heavy metals and nitrite and nitrate. At the same time, clam shell was known as a low-cost and effective pollutant adsorbent that could remove pollutant from the water. This study aimed to model the removal efficiency of clam shell of Perna viridis on copper, zinc, nitrate, and nitrite pollutants from waste water. The model is using the structural equation model.METHODS: The pollutants observed included copper, zinc, nitrate, and nitrite, considering that those pollutants are common pollutants occurring in aquaculture wastewater. For producing the clam shell adsorbent, the procedures include calcination of clam shells. The modeling analysis to model the pollutant removal efficiency by clam shell was done using the Structural Equation Model method using latent and observed variables. The determinant water variables affecting removal efficiency were total suspended solid, total alkalinity, and potential hydrogen. The model were then validated using the factor loadings.FINDINGS: The result showed clam shell can reduce the heavy metals from water with a removal efficiency of 84–99 percent. According to model results and factor loading values, water variables that contribute significantly to the metal removals were total alkanility, followed by potential hydrogen. Metal that was affected significantly by those water variables was copper. This is also similar for nitrite and nitrate in water, with nitrite being more affected.CONCLUSION: In general, clam shell can adsorb diluted pollutants from aquaculture wastewater since there are portions of adsorbed pollutants. The modeling approach is very useful to inform and distinguish particular water variables that may affect the efficiency of pollutant removals by clam shell from wastewaters.